Novel methylene blue staining technique for localizing small esophageal leiomyomas during thoracoscopic enucleation. Issue 8 (6th November 2015) - Zhang, Z.; Ai, B.; Liao, Y.; Liu, L.; Liu, M.
Abstract : Summary: The treatment of choice for leiomyoma, the most common benign esophageal tumor, is thoracoscopic enucleation. One of the most difficult aspects of thoracoscopic enucleation is the precise localization of small tumors (≤1.5 cm) and tumors without external protrusion. No simple, feasible solutions to this problem are available. We developed a novel methylene blue staining technique to localize small esophageal leiomyomas and evaluated the feasibility of our technique. Between January 2013 and July 2014, eight patients with small esophageal leiomyomas (≤1.5 cm) underwent thoracoscopic enucleation in Tongji Hospital. Preoperative endoscopic ultrasonography was performed in all patients. The leiomyomas were located in the middle ( n = 5) and lower ( n = 3) thirds of the esophagus. We preoperatively injected 0.5–1.0 mL methylene blue in the submucosa adjacent to the tumors under standard gastroscope guidance. The entire staining process took about 10 minutes. Staining was successful in all patients. The unstained tumor was exposed after the blue‐stained mediastinal pleura, and overlying muscle were incised longitudinally. All procedures were successfully completed without conversion to open surgery. No abnormalities were detected in the esophageal mucosa. The median operating time was 60 minutes (range, 40–90 minutes). Postoperative histopathology confirmed leiomyoma in all patients. The median postoperative hospital stay was 6 days (range, 5–7 days). No major complications, such as esophageal leakage or esophageal diverticulum, occurred. Endoscopic methylene blue staining is safe and feasible for localizing small esophageal leiomyomas during thoracoscopic enucleation. This method will enable precise and easy enucleation.